Analisa Kepuasan Pelanggan Terhadap Pelayanan di Toko XX di Gunungsitoli - Zebua, Yesni Anggraini (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Customer satisfaction is an important indicator in evaluating business success. Toko XX in Gunungsitoli has the responsibility to ensure that customers are satisfied with their services. This study uses a quantitative method with a survey approach and the SERVQUAL model to measure customer satisfaction. A sample of 385 respondents was randomly selected. The results of the study show that customers are generally satisfied, with 60% giving a rating of 4 (satisfied) and 20% giving a rating of 5 (very satisfied). The dimensions of reliability and responsiveness have a significant impact on customer satisfaction, while the dimensions of tangibles and empathy need improvement. These findings provide insights for Toko XX to improve service quality and customer satisfaction